Hubungan Karakteristik, Pengetahuan dan Literasi Kesehatan dengan Praktik Deteksi Dini Kanker payudara pada Wanita Usia Subur - Erawatul Endah Nurfitri (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2022)
Background: Cancer is a deadly disease for humans. As such, early detection of breast cancer is important as a precautionary measure against it. Health Literacy is one of factors influencing a person's behavior. The purpose of this research is to analyze the relationship between characteristics, knowledge, and Health Literacy with practices of early breast cancer detection in women of childbearing age in the working area of Temanggung health center at Temanggung regency in 2019. Method: A quantitative research method was used in this research with a sample of 98 respondents. The instruments used in this research were questionnaires consisting of HL EU 12 Q questionnaire, knowledge questionnaire, and BSE practice. Result: The research results show that the age of women was still reproductive, 93.9% had no family/relatives medical history, 58.2% of respondents were highly educated, 91.8% had jobs in the non-health field, 56.1% had high income and 84.7% had access information. 58.0% had good knowledge. A total of 68.4% had high Health Literacy. The relation results show that no relation between age and family/relatives medical history with practices of early breast cancer detection, there is a relation between education, employment, access information, knowledge and Health Literacy with practices of early breast cancer detection. Implication: Women should be more concerned about health, especially regarding the prevention of breast cancer, thus the incidence of breast cancer will decline.